Sperm count is increased by diet-induced weight loss and maintained by exercise or GLP-1 analogue treatment: a randomized controlled trial. Issue 7 (17th May 2022) - Andersen, Emil; Juhl, Christian R; Kjøller, Emma T; Lundgren, Julie R; Janus, Charlotte; Dehestani, Yasmin; Saupstad, Marte; Ingerslev, Lars R; Duun, Olivia M; Jensen, Simon B K; Holst, Jens J; Stallknecht, Bente M; et al.
Abstract: STUDY QUESTION: Does diet-induced weight loss improve semen parameters, and are these possible improvements maintained with sustained weight loss? SUMMARY ANSWER: An 8-week low-calorie diet-induced weight loss was associated with improved sperm concentration and sperm count, which were maintained after 1 year in men who maintained weight loss. WHAT IS KNOWN ALREADY: Obesity is associated with impaired semen quality. Weight loss improves metabolic health in obesity, but there is a lack of knowledge on the acute and long-term effects of weight loss on semen parameters. STUDY DESIGN, SIZE, DURATION: This is a substudy of men with obesity enrolled in a randomized, controlled, double-blinded trial (the S-LITE trial). The trial was conducted between August 2016 and November 2019. A total of 56 men were included in the study and assigned to an initial 8-week low-calorie diet (800 kcal/day) followed by randomization to 52 weeks of either: placebo and habitual activity (placebo), exercise training and placebo (exercise), the Glucagon Like Peptide 1 (GLP-1) analogue liraglutide and habitual activity (liraglutide) or liraglutide in combination with exercise training (combination). PARTICIPANTS/MATERIALS, SETTING, METHODS: Inclusion criteria were men who delivered semen samples, 18 to 65 years of age, and a body mass index between 32 and 43 kg/m 2, but otherwise healthy. The study was carried out at Hvidovre Hospital and at the University of Copenhagen, and the participants were from the Greater Copenhagen Area. We assessed semen parameters and anthropometrics and collected blood samples before (T0), after the 8-week low-calorie dietary intervention (T1), and after 52 weeks (T2). MAIN RESULTS AND THE ROLE OF CHANCE: The men lost on average 16.5 kg (95% CI: 15.2–17.8) body weight during the low-calorie diet, which increased sperm concentration 1.49-fold (95% CI: 1.18–1.88, P < 0.01) and sperm count 1.41-fold (95% CI: 1.07–1.87, P < 0.01). These improvements were maintained for 52 weeks in men who maintained the weight loss, but not in men who regained weight. Semen volume, sperm motility and motile sperm count did not change. LIMITATIONS, REASONS FOR CAUTION: The S-LITE trial was a randomized controlled trial of weight loss maintenance. Analysis of semen was preregistered to explore the effects of weight loss and weight loss maintenance on semen parameters, but definite inferences cannot be made. WIDER IMPLICATIONS OF THE FINDINGS: This study shows that sperm concentration and sperm count were improved after a diet-induced weight loss in men with obesity. Our findings indicate that either or both liraglutide and exercise as weight maintenance strategies may be used to maintain the improvements in sperm concentration and count. STUDY FUNDING/COMPETING INTEREST(S): This work is supported by an excellence grant from the Novo Nordisk Foundation (NNF16OC0019968), a Challenge Programme Grant from the Novo Nordisk Foundation (NNF18OC0033754) and a grant from Helsefonden. The Novo Nordisk Foundation Center for Basic Metabolic Research is an independent research centre at the University of Copenhagen, partially funded by an unrestricted donation from the Novo Nordisk Foundation (NNF18CC0034900). Saxenda (liraglutide) and placebo pens were provided by Novo Nordisk. Cambridge Weight Plan diet products for the 8-week low-calorie diet were provided by Cambridge Weight Plan. E.A.: shareholder, employee of ExSeed Health Ltd. Grant Recipient from ExSeed Health Ltd and listed on Patents planned, issued or pending with ExSeed Health Ltd; J.J.H.: consultant for Eli Lilly A/S and Novo Nordisk A/S. Lecture fees for Novo Nordisk A/S. Listed on Patents planned, issued or pending with the University of Copenhagen, Advocacy group for Antag Therapeutics and Bainan Biotech; S.M.: lecture fees for Novo Nordisk A/S. Recipient of Support for attending meetings from Novo Nordisk A/S. Advisory boards of Novo Nordisk A/S; Sanofi Aventis and Merck Sharp & Dohme. S.S.T.: research grant recipient Novo Nordisk. The remaining authors have no conflicts of interest to declare. TRIAL REGISTRATION NUMBER: The trial was approved by the Ethical Committee of the Capital Region of Denmark (H-16027082) and the Danish Medicines Agency (EudraCT Number: 2015-005585-32). ClinicalTrials.gov identifier (NCT number): NCT04122716. TRIAL REGISTRATION DATE: 11 May 2016. DATE OF FIRST PATIENT'S ENROLMENT: August 2016.